Management and bioremediation of hydrocarbon-polluted soils in Antarctica - Ruberto, Lucas Adolfo Mauro; Martinez Alvarez, Lucas Manuel; Massot, Francisco; MacCormack, Walter P.
Until a few years ago, the Antarctic continent was considered a pristine place. However, human activity there changed that condition, being hydrocarbon pollution a concerning and attention-drawing issue. Soils around scientific stations show different levels of pollution caused by oil-derived fuels, such as gasoil. Bioremediation is a tested, effective technique to remove contaminating hydrocarbon from the soil. Biostimulated biopiles is the most effective, tested strategy for Antarctic soils that makes use of the microorganisms’ catabolic potential; ecopiles, in turn, seem to be a better alternative that brings more complex biological systems into the process, such as vascular plants, in order to obtain higher removal levels. Finally, a reflection is made that appropriate, specific logistics are needed to reduce execution times of these innovative bioremediation treatments. Fil: Ruberto, Lucas Adolfo Mauro. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Martinez Alvarez, Lucas Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Massot, Francisco. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Nanobiotecnología. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Nanobiotecnología; Argentina Fil: MacCormack, Walter P. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina